Analisis Yuridis Putusan Hakim Pengadilan Negeri Padang Nomor 69/Pdt.SuBPSK/2025/PN Tentang Sengketa Pembiayaan Multiguna - Citra Maharani; Helfira Citra (GLOBAL SCIENTS PUBLISHER, 2025)
Consumer Financing is a form of consumer financing provided to the publicias an alternative to fulfilling the need for goods or services based on Sharia principles, accompanied by collateral in the form of valuable items such as SHM, SHGB, or BPKB. This financing is a solution for people who need funds quickly. According to the Minister of Finance Regulation Number 84/PMK.012/2006 concerning Financing Companies, a Financing Institution, according to the Financial Services Authority, is a business entity that carries out financing activities in the form of providing funds or capital goods. Based on this, this study aims to review the Padang District Court Decision Number 69/Pdt.SuBPSK/2025/PN and to identify the obstacles encountered in Multipurpose Financing Disputes with Fiduciary Guarantees Through Installment Purchases that have Arose as Default Disputes (Padang District Court Decision Number 69/Pdt.SuBPSK/2025/PN Pdg). The research method was qualitative and used a normative juridical approach. The data used is primary data with secondary legal materials through decisions and literature studies. The resultsiof the study show that the Petitioner's objection request in its entirety, states that the Consumer Dispute Resolution Agency (BPSK) of Padang City, West Sumatra Province is not authorized to examine and adjudicate the a quo case and cancels the Decision of the Consumer Dispute Resolution Agency (BPSK) of Padang City, West Sumatra Province Number: 04 / PTS / BPSK-PDG / SBR / ARBT / III / 2025, the Respondent has committed a breach of contract, the fiduciary guarantee certificate number: W3.00106938.AH.05.01 YEAR 2023 is valid, the handover of the fiduciary guarantee object in the form of one unit of Honda Scootermatic motorbike in 2023 is valid and the Supreme Court of the Republiciof Indonesia Sentences the Respondent to pay all costs arising in this case amount ngito Rp164,000.00 (one hundred and sixty four thousand rupiah). Obstacles encountered in resolving fiduciary disputes can be both internaliand external. Internal obstaclesirelate to employees' lack of understanding and knowledge regardin ifiduciary-related multipurpose financing, limited budgets for case handling, and potentially inefficient internal processes. External obstacles include third-party intervention, difficulties in collecting collateral, and a lack of public awareness regarding fiduciary-related multipurpose financing.